2010
DOI: 10.1097/ajp.0b013e3181bff86d
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Analgesic Effect of Ketamine in Patients Undergoing Elective Cesarean Section

Abstract: Intraoperative low-dose ketamine had no effect on morphine consumption during 2 to 24 hours after surgery. No significant differences were seen in the pain scores of the 2 groups during the study period. The preoperative administration of 0.5 mg/kg ketamine in patients undergoing cesarean section did not elicit a preemptive analgesic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 30 publications
2
44
1
7
Order By: Relevance
“…According to inclusion criteria in our analysis, a total of five English studies 13,[17][18][19][20] matched the selection criteria finally (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…According to inclusion criteria in our analysis, a total of five English studies 13,[17][18][19][20] matched the selection criteria finally (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…These study results of Nesek-Adam et al 20 were all no statistically significant. Lenzmeier et al 19 and Reza et al 13 assessed the postoperative pain scores of ketamine at a dosage of 0.50 mg/kg. Lenzmeier et al 19 reported that the postoperative pain score (p<0.05) at post-anaesthesia care unit (PACU) were lower in ketamine group than that in control group but no significant difference were found among the two groups for the postoperative pain intensity when the patients discharged from hospital.…”
Section: Postoperative Pain Scorementioning
confidence: 99%
See 3 more Smart Citations